Community participation in the management of the Nong Peung wetland: A case study of Ban Pak Peung, Paksan District, Bolikhamxay Province - PHANTHVONG, Phitsanou; TANSAVATH, Malaphone; PHOMPILA, Chittana; ACKHAVONG, Somsanook; PHENGVICHITH, Vansaleum (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The purpose of this study was to assess the participation of local residents in the Urban Ebs Lao PDR project activities related to the management of the Nong Peung Wetland in Pakpeung Village, Paksan District, Borikhamxay Province. Data were collected through interviews with members of the project management committee, village authorities, and a sample of 105 households. The data were analyzed using Microsoft Excel to determine frequencies, percentages (%), and average ( x ̅) The results showed that villagers in Pakpeung participated in activities related to establishing responsible units for water management, ensuring flood prevention during the rainy season, and maintaining an adequate water supply during the dry season. These activities included three sub-activities coordinated at both the central and village levels, with villagers participating an average of 39 times per person per activity. The survey and removal of sediment and waste obstructing water flow included seven sub-activities, of which villagers participated more actively in five, totaling 40 times per person per activity (x̅ = 1.90, 38.10%). Participation in the activity of monitoring residual chemicals and enforcing control measures averaged (x̅ = 3.42, 68.57%), while the activity of hiring fishing boats to collect garbage from water sources showed a high level of participation (x̅ = 4.33, 86%). Additionally, there were activities concerning the approval of land-use changes in accordance with land laws. The project planned two sub-activities, both of which were completed by 2025, with an average implementation rate of 15.38%. However, it was also found that the rules and regulations for managing land use within the Nong Peung watershed have not been effectively enforced. Overall, while the planned activities could be implemented successfully, the level of public participation in these activities was considered low.